A Clinical Comparison of EMLA Cream and Ethyl Chloride Spray Application for Pain Relief of Forehead Botulinum Toxin Injection. Issue 3 (September 2015) - Irkoren, Saime; Ozkan, Heval Selman; Karaca, Huray
Abstract : Objectives: This study aims to analyze the efficiency of EMLA cream and ethyl chloride spray application for pain alleviation before botulinum toxin injection. Methods: Forty-five patients were divided into 3 treatment groups. Skin cooling with ethyl chloride spray (in group 1), topical anesthetic cream (EMLA) (in group 2), was used on the forehead area on one side previous to injection; the opposite side served as the control. In the third group (n = 15), cold was applied using ethyl chloride spray to one side, and to the other side topical anesthetic cream (EMLA) was applied. A visual analog scale was used for pain intensity. Results: In the first group, the average pain score was 3.20 ± 1.20 on the side where ethyl chloride spray was applied and 7.26 ± 1.94 on the control side ( P < 0.05). It was 4.20 ± 1.37 on the side receiving EMLA and 7.66 ± 1.54 ( P < 0.05) on the control side in the second group. In the third group, the average score was 6.80 ± 1.37 for the EMLA side and 2.93 ± 1.03 for the ethyl chloride sprayed side ( P < 0.05). Conclusions: Skin cooling with ethyl chloride spray significantly decreases the pain associated during forehead botulinum toxin injections.